Stability of feed enzymes in physiological conditions assayed by in vitro methods - Johan Inborr; Anne Grönlund (Agricultural and Food Science, 1993)
A series of in vitro incubations were carried out to investigate the stability of two enzyme preparations in conditions similar to those in the upper gastrointestinal tract of monogastric animals. The two enzyme products, one crude xylanase from Trichoderma longibrachiatum (Multifekt K) and the other a specifically manufactured feed enzyme (Avizyme SX®), were subjected to incubations at low and neutral pH with and without proteolytic enzymes (pepsin and pancreatin). Wheat gluten was employed together with the crude xylanase to investigate its potential as a stabilising agent. Due to the buffering effect of Avizyme SX®, incubations were carried out with (pH 2.5) and without (pH 3.2) addition of either citric or hydrochloric acid. Incubation of the crude xylanase at low pH followed by incubation at neutral pH resulted in negligible loss of xylanase activity whereas β-xylosidase recovery fell to 57 per cent of the initial value (P